FAKTOR - FAKTOR RISIKO USIA, ASUPAN TABLET FE DAN STATUS GIZI YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Waode Sitti Asfiah Udu; Andi Yulia; Sitti Wahidatun Asryani (Halu Oleo University, 2014)
Gravidarum anemia can increase the risk of mortality in pregnancy . The prevalence of gravidarum anemia in world is high especially in developing country according to data of WHO. This study aimed to identify the gravidarum anemia risk factors such age, Fe tablet consumption and nutritional status in pregnant woman at Poasia’s society health center region of Kendari City. This study used an analytical study with case control design. The case groups in this study are 40 pregnant woman with gravidarum anemia who have Hb<11 gr/dL while pregnant woman with Hb ≥ 11 gr/dL are used as control. Risk factor is assessing by Odds ratio. This study founded that age have OR = 7.21 (1.48-35.06; 95%), Fe tablet consumption have OR = 27.0 (7.68-94.87; 95%) and nutritional status have OR = 1.92 (0.69-5.33; 95%). As conclusions, age and Fe tablet consumption are risk factors for gravidarum anemia while nutritional status is not a risk factor for gravidarum anemia. Key words: Gravidarum anemia, age, Fe tablet consumption, nutritional status.